Method for optimizing hybrid insulator silicone rubber adhesive, adhesive and hybrid insulator

CN122991387APending Publication Date: 2026-10-27CHINA ELECTRIC POWER RESEARCH INSTITUTE CO LTD +3
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202610929771.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-06-25
Publication Date
2026-10-27

AI Technical Summary

Technical Problem

而现有硅橡胶粘接剂未针对户外严苛服役环境进行分子结构定向优化设计,分子结构稳定性不足,在多因素环境老化作用下,极易出现分子主链降解、侧链水解断裂、交联网络破损等问题,最终导致粘接界面粘接强度大幅衰减、界面脱粘、密封失效,引发绝缘子运行故障,严重制约了高压、特高压输电线路的长期安全稳定运行

Benefits of technology

[0024]综上所述,本发明的有益技术效果为:本申请提供的混合绝缘子硅橡胶粘接剂优化方法、粘接剂及混合绝缘子的有益技术效果为:(1)通过分子动力学模拟,建立了粘接剂分子结构参数与宏观界面性能(界面结合能、耐老化性)之间的定量关联,实现了从分子层面的定向、理性设计;由此获得的粘接剂分子结构兼具高界面相容性和优异的耐环境老化能力,从源头上确保了产品性能的优越性。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122991387A_ABST
    Figure CN122991387A_ABST
Patent Text Reader

Abstract

The application relates to a mixed insulator silicone rubber adhesive optimization method, an adhesive and a mixed insulator. The optimization method comprises the following steps: constructing an interface molecular model of high-temperature vulcanized silicone rubber and a silicone rubber adhesive, calculating interface binding energy through molecular dynamics simulation, simulating an aging process under a high-temperature, high-humidity and ultraviolet radiation environment, screening and determining the optimal molecular structure of the silicone rubber adhesive based on the interface binding energy and the aging simulation result; preparing adhesive compound by using the optimal molecular structure, and curing the adhesive compound by using a gradient curing process. The gradient curing process comprises a pre-curing stage, a stress release stage, a main curing stage and a post-curing stage in sequence. The quantitative correlation between the adhesive molecular structure parameters and the macroscopic interface performance is established through molecular dynamics simulation, and the adhesive molecular structure obtained has high interface compatibility and excellent environmental aging resistance, thereby ensuring the superiority of product performance from the source.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the fields of polymer material preparation and electrical equipment insulation technology, and in particular to an optimized method for silicone rubber adhesive for hybrid insulators, the adhesive, and hybrid insulators. Background Technology

[0002] Currently, composite insulators are core insulation equipment for high-voltage and ultra-high-voltage transmission lines. They are mainly composed of high-strength glazed ceramic core rods, high-temperature vulcanized (HTV) silicone rubber sheds, and end metal accessories. Composite insulators have outstanding advantages such as light weight, high mechanical strength, excellent surface hydrophobicity, and resistance to pollution flashover. They can effectively adapt to the transmission operation requirements under complex climates and operating conditions. They are now widely and routinely used in high-voltage and ultra-high-voltage transmission networks at all levels in China and are key equipment to ensure the stable operation of transmission lines.

[0003] In the overall structure of a hybrid insulator, the bonding interface between the silicone rubber shed sheath and the ceramic core rod and end metal fittings is the core weakest point. The bonding strength, sealing performance, structural stability, and aging resistance of this interface directly determine the overall mechanical properties, sealing reliability, and long-term service life of the hybrid insulator. Once the bonding interface fails, it will directly lead to faults such as insulator shed detachment, sealing failure, and decreased insulation performance, seriously threatening the safe and stable operation of transmission lines. At present, the connection between the silicone rubber shed sheath and the core rod or metal fittings relies on a special silicone rubber adhesive for bonding and fixing. The adhesive formulation and matching curing process are the core factors determining the overall performance of the bonding interface.

[0004] Currently available commercial silicone rubber adhesives and their supporting application processes have gradually revealed many inherent technical defects in long-term engineering applications, making it difficult to meet the service requirements of transmission lines under ultra-long cycles and harsh environments. Firstly, existing silicone rubber adhesives have poor interfacial compatibility with HTV silicone rubber matrices, and the matching degree of their interfacial bonding performance is insufficient. This not only leads to low initial bonding strength but also easily forms a weak boundary layer at the bonding interface, fundamentally reducing the basic reliability of the bonded structure.

[0005] Secondly, traditional bonding and curing processes often employ a one-step high-temperature curing method. This process results in an excessively rapid cross-linking reaction rate, causing the bonding interface to undergo high-strength cross-linking and curing within a short period. Consequently, the internal stress generated during the reaction cannot be released promptly and fully, leading to numerous microscopic defects and microcracks remaining within the bonding interface, creating hidden damage. These microscopic defects will continue to expand and extend during the long-term service life of the insulator, gradually developing into potential structural failure hazards and significantly shortening the safe service life of the insulator.

[0006] Third, high-voltage transmission lines are mostly located in outdoor environments, where the bonding interfaces must withstand the combined effects of multiple complex environmental stresses, including high-temperature exposure, high-humidity rain, ultraviolet radiation, diurnal temperature cycles, and acid rain erosion. Existing silicone rubber adhesives lack molecular structure optimization for these harsh outdoor service environments, resulting in insufficient molecular stability. Under the influence of various environmental aging factors, they are prone to problems such as main chain degradation, side chain hydrolysis and breakage, and cross-linking network damage. This ultimately leads to a significant decrease in bonding strength, interface debonding, and sealing failure, causing insulator malfunctions and severely restricting the long-term safe and stable operation of high-voltage and ultra-high-voltage transmission lines.

[0007] To address the aforementioned issues of insufficient adhesive interface performance and susceptibility to aging failure, current industry-standard improvement methods primarily focus on adjusting local parameters such as adding silane coupling agents, modifying the ratio of inorganic fillers, and slightly optimizing curing temperature and time. These methods are all trial-and-error optimizations based on engineering experience, only offering minor improvements to adhesive performance. They fail to address the root causes of poor interfacial compatibility and insufficient initial bond strength by focusing on the fundamental molecular structure of the adhesive and the core mechanisms of interfacial failure through targeted design and systematic optimization.

[0008] Meanwhile, in existing technologies, adhesive formulation optimization and curing process optimization are carried out independently and disconnected, failing to form an integrated solution encompassing "molecular structure design, curing process matching, and performance verification and evaluation." This approach cannot effectively balance the core contradiction between interfacial stress release and long-term aging resistance and durability, resulting in limited improvement effects and poor stability. In summary, the field currently lacks a complete technical solution that achieves targeted optimization at the molecular level, precise process matching, and systematic performance enhancement, making it difficult to thoroughly address the industry pain points of early failure and insufficient long-term reliability at the bonding interface of hybrid insulators. Summary of the Invention

[0009] To address the shortcomings of existing technologies, the present invention aims to provide an optimized method for silicone rubber adhesives for hybrid insulators, an adhesive, and hybrid insulators. Its advantages are that it can guide the design of adhesive molecular structures through molecular simulation and be coupled with a specialized gradient curing process to obtain adhesive products with excellent interfacial properties and aging resistance.

[0010] The above-mentioned objective of this invention is achieved through the following technical solution: In one aspect, this invention provides a method for optimizing silicone rubber adhesives for hybrid insulators, comprising the following steps: S1. Construct an interfacial molecular model of high-temperature vulcanized silicone rubber and silicone rubber adhesive, calculate the interfacial binding energy through molecular dynamics simulation, and simulate the aging process under high temperature, high humidity and ultraviolet radiation environment. Based on the interfacial binding energy and aging simulation results, screen and determine the optimal molecular structure of silicone rubber adhesive. S2. The adhesive compound is formulated using the optimal molecular structure determined in step S1, and the adhesive compound is cured using a gradient curing process, which includes a pre-curing stage, a stress release stage, a main curing stage, and a post-curing stage in sequence.

[0011] Preferably, in the method for optimizing the silicone rubber adhesive for hybrid insulators provided by the present invention, in step S1, the optimal molecular structure is a modified siloxane oligomer, wherein the main chain of the modified siloxane oligomer is modified with phenyl or trifluoropropyl groups, the side chain is modified with hydrolyzable silane groups, and the end group is modified with vinyl crosslinking sites.

[0012] Preferably, in the method for optimizing the silicone rubber adhesive for hybrid insulators provided by the present invention, the modified siloxane oligomer contains phenyl or trifluoropropyl modified structural units accounting for 5%-20% of the total structural units, side chains containing hydrolyzable silane groups accounting for 1%-5% of the total side chains, and end groups containing vinyl groups accounting for 0.5%-2% of the total end groups.

[0013] Preferably, in the method for optimizing the silicone rubber adhesive for hybrid insulators provided by the present invention, the simulated environmental parameters in step S1 are as follows: the high temperature condition is 150℃-200℃, the high humidity condition is a relative humidity of 85%-95%, and the ultraviolet radiation condition is the use of a UVA-340 fluorescent ultraviolet lamp with an irradiance of 0.35 W / m at a wavelength of 340nm. 2 ~1.5 W / m 2 .

[0014] Preferably, in the method for optimizing the silicone rubber adhesive for hybrid insulators provided by the present invention, the preparation process of the adhesive compound in step S2 includes: Based on the functional group composition corresponding to the optimal molecular structure determined in step S1, select the corresponding cyclosiloxane monomers and carry out ring-opening copolymerization reaction under the action of a catalyst to synthesize modified siloxane polymer-based raw rubber. Based on 100 parts by weight of the raw rubber, add 40-50 parts by weight of fumed silica, 3-5 parts by weight of coloring stabilizer, and 1-2 parts by weight of peroxide curing agent, and mix evenly at room temperature to obtain an adhesive compound with uniform texture and color.

[0015] Preferably, in the optimized method for the mixed insulator silicone rubber adhesive provided by the present invention, the coloring stabilizer is iron oxide red, and the peroxide curing agent is 2,5-dimethyl-2,5-di(tert-butylperoxy)hexane.

[0016] Preferably, the method for optimizing the silicone rubber adhesive for hybrid insulators provided by the present invention, based on the functional group composition corresponding to the optimal molecular structure determined in step S1, selects the corresponding cyclosiloxane monomers and performs a ring-opening copolymerization reaction under the action of a catalyst to synthesize modified siloxane polymer-based raw rubber, comprising: Based on the functional group composition corresponding to the optimal molecular structure, octamethylcyclotetrasiloxane and cyclosiloxane monomers containing phenyl or trifluoropropyl groups were selected and combined with silane coupling agents containing hydrolyzable groups. Under the action of a catalyst, a ring-opening copolymerization reaction was carried out to synthesize modified siloxane polymer-based raw rubber with target chain segments and functional groups.

[0017] Preferably, the optimized method for hybrid insulator silicone rubber adhesive provided by the present invention includes, in step S2, a gradient curing process comprising: Pre-curing stage: Curing at 60℃-80℃ for 1-2 hours; Stress release stage: The temperature is gradually increased from the pre-curing temperature gradient to 80℃-100℃, and then kept at the temperature in sections within this temperature range for a total duration of 1-3 hours. Main curing stage: Heat to 120℃-150℃ and cure for 4-6 hours; Post-curing stage: Heat treatment at 150℃-180℃ for 1-2 hours.

[0018] Preferably, the method for optimizing the silicone rubber adhesive for hybrid insulators provided by the present invention further includes step S1: establishing a quantitative relationship model between molecular structure parameters and aging performance.

[0019] Preferably, the method for optimizing the silicone rubber adhesive for hybrid insulators provided by the present invention further includes step S3: Based on the quantitative relationship model and combined with the non-destructive testing results of the bond interface after curing, the aging state of the bond interface is evaluated.

[0020] Preferably, the method for optimizing the silicone rubber adhesive for hybrid insulators provided by the present invention includes at least one of ultrasonic testing, X-ray imaging, and dielectric spectrum analysis.

[0021] Preferably, in the method for optimizing the silicone rubber adhesive for hybrid insulators provided by the present invention, the molecular dynamics simulation in step S1 is performed using the COMPASS force field.

[0022] On the other hand, the present invention provides a hybrid insulator silicone rubber adhesive, which is prepared by the above-described optimized method for hybrid insulator silicone rubber adhesive.

[0023] On the other hand, the present invention provides a hybrid insulator including a core rod, a skirt sheath, and end metal fittings, wherein the skirt sheath is connected to the core rod and / or the metal fittings by an adhesive layer, the adhesive layer being formed by curing the aforementioned hybrid insulator silicone rubber adhesive.

[0024] In summary, the beneficial technical effects of the present invention are as follows: The beneficial technical effects of the optimized method for silicone rubber adhesive for hybrid insulators, the adhesive and the hybrid insulator provided in this application are as follows: (1) Through molecular dynamics simulation, a quantitative correlation between the molecular structure parameters of the adhesive and the macroscopic interface properties (interface bonding energy, aging resistance) is established, realizing directional and rational design at the molecular level; the adhesive molecular structure obtained thereby has both high interfacial compatibility and excellent environmental aging resistance, ensuring the superior performance of the product from the source.

[0025] (2) The gradient curing process developed achieves the coordinated regulation of cross-linking network formation and internal stress relaxation through precise temperature and time control in four stages: pre-curing, stress release, main curing and post-curing. The stress release stage effectively eliminates residual stress at the interface, significantly improving the intrinsic strength and long-term service reliability of the bonding interface.

[0026] (3) By combining the quantitative aging model established by molecular simulation with non-destructive testing technology, a method for early diagnosis and life prediction of the bonding interface state has been formed. This provides key technical support for realizing the intelligent operation and maintenance of hybrid insulators from "periodic maintenance" to "predictive maintenance", which helps to reduce the total life cycle cost. Attached Figure Description

[0027] Figure 1 This is a flowchart of the method for optimizing the silicone rubber adhesive for hybrid insulators provided in an embodiment of the present invention. Detailed Implementation

[0028] The present invention will be further described in detail below with reference to the accompanying drawings.

[0029] Where 1 part by weight = 1g.

[0030] Example 1: Reference Figure 1 This embodiment provides an optimization method for silicone rubber adhesives used in hybrid insulators, comprising the following steps: S1. In Materials Studio, interface models were constructed between an HTV silicone rubber substrate and five candidate adhesives (models AE). Model D is a modified siloxane oligomer with a main chain containing 8% diphenylsiloxane and 5% methyltrifluoropropylsiloxane, and a side chain containing 2% γ-aminopropyltriethoxysilane. Molecular dynamics simulations were performed using the COMPASS II force field to calculate the interfacial binding energy. Aging simulations were then conducted under simulated conditions of 175℃ high temperature, 90%RH high humidity, and 0.68 W / m² @340nm UV radiation. Simulation results showed that Model D exhibited the slowest decay rate of interfacial binding energy under comprehensive aging conditions, demonstrating the best interfacial durability. Therefore, based on the initial value of the interfacial binding energy and the aging simulation results, the molecular structure represented by Model D was selected as the optimal molecular structure.

[0031] S2. Following the structure of Model D, a modified siloxane polymer-based adhesive (raw rubber) was synthesized using octamethylcyclotetrasiloxane (80 parts by weight), tetramethyltetraphenylcyclotetrasiloxane (15 parts by weight), trifluoropropylmethylcyclotrisiloxane (8 parts by weight), and γ-aminopropyltriethoxysilane (2 parts by weight) as main raw materials under the catalysis of tetramethylammonium hydroxide. 100 parts by weight of this raw rubber were then mixed with 40 parts by weight of fumed silica, 5 parts by weight of iron oxide red, and 1.5 parts by weight of the peroxide curing agent 2,5-dimethyl-2,5-di(tert-butylperoxy)hexane, and the mixture was thoroughly stirred to obtain the adhesive compound.

[0032] The gradient curing process was used to cure it with HTV silicone rubber: the test pieces were prepared by sequentially treating it at 70℃ / 1.5h (pre-curing), increasing the temperature to 90℃ at 0.5℃ / min and holding it at the temperature in sections for 2h (stress release), 140℃ / 5h (main curing), and 165℃ / 1h (post-curing).

[0033] Example 2: This embodiment provides an optimization method for silicone rubber adhesives used in hybrid insulators, including the following steps: S1. In Materials Studio, interface models were constructed between an HTV silicone rubber substrate and five candidate adhesives (models AE). Model D is a modified siloxane oligomer with a main chain containing 5% diphenylsiloxane and 1% methyltrifluoropropylsiloxane, and a side chain containing 0.5% γ-aminopropyltriethoxysilane. Molecular dynamics simulations were performed using the COMPASS II force field to calculate the interfacial binding energy. Aging simulations were then conducted under simulated conditions of 150℃ high temperature, 85%RH high humidity, and 0.35 W / m² @340nm UV radiation. Simulation results showed that model D exhibited the slowest decay rate of interfacial binding energy under comprehensive aging conditions, demonstrating the best interfacial durability. Therefore, based on the initial value of the interfacial binding energy and the aging simulation results, the molecular structure represented by model D was selected as the optimal molecular structure.

[0034] S2. Following the structure of Model D, a modified siloxane polymer-based adhesive (raw rubber) was synthesized using octamethylcyclotetrasiloxane (85 parts by weight), tetramethyltetraphenylcyclotetrasiloxane (8 parts by weight), trifluoropropylmethylcyclotrisiloxane (1.5 parts by weight), and γ-aminopropyltriethoxysilane (1 part by weight) as main raw materials under the catalysis of tetramethylammonium hydroxide. 100 parts by weight of this raw rubber were then mixed with 50 parts by weight of fumed silica, 3 parts by weight of iron oxide red, and 1 part by weight of the peroxide curing agent 2,5-dimethyl-2,5-di(tert-butylperoxy)hexane, and the mixture was thoroughly stirred to obtain the adhesive compound.

[0035] The process involves using a gradient curing technique to cure HTV silicone rubber: the mixture is cured sequentially at 60℃ / 1h (pre-curing), then at 0.5℃ / min to 80℃ and held at that temperature for 1h in stages (stress release), then at 120℃ / 4h (main curing), and finally at 150℃ / 1h (post-curing) to obtain bonded test pieces.

[0036] Example 3: This embodiment provides an optimization method for silicone rubber adhesives used in hybrid insulators, including the following steps: S1. In Materials Studio, interface models were constructed between an HTV silicone rubber substrate and five candidate adhesives (models AE). Model D is a modified siloxane oligomer with a main chain containing 20% ​​diphenylsiloxane and 5% methyltrifluoropropylsiloxane, and a side chain containing 0.5% γ-aminopropyltriethoxysilane. Molecular dynamics simulations were performed using the COMPASS II force field to calculate the interfacial binding energy. Aging simulations were then conducted under simulated conditions of 200℃ high temperature, 95%RH high humidity, and 1.5 W / m² @340nm UV radiation. Simulation results showed that model D exhibited the slowest decay rate of interfacial binding energy under comprehensive aging conditions, demonstrating the best interfacial durability. Therefore, based on the initial value of the interfacial binding energy and the aging simulation results, the molecular structure represented by model D was selected as the optimal molecular structure.

[0037] S2. Following the structure of Model D, a modified siloxane polymer-based adhesive (raw rubber) was synthesized using octamethylcyclotetrasiloxane (65 parts by weight), tetramethyltetraphenylcyclotetrasiloxane (28 parts by weight), trifluoropropylmethylcyclotrisiloxane (8 parts by weight), and γ-aminopropyltriethoxysilane (5 parts by weight) as main raw materials under the catalysis of tetramethylammonium hydroxide. 100 parts by weight of this raw rubber were then mixed with 40 parts by weight of fumed silica, 5 parts by weight of iron oxide red, and 2 parts by weight of the peroxide curing agent 2,5-dimethyl-2,5-di(tert-butylperoxy)hexane, and the mixture was thoroughly stirred to obtain the adhesive compound.

[0038] The process involved curing the HTV silicone rubber using a gradient curing technique: the rubber was cured sequentially at 80℃ / 2h (pre-curing), then at 0.5℃ / min to 100℃ and held at that temperature for 3h in sections (stress release), then at 150℃ / 6h (main curing), and finally at 180℃ / 2h (post-curing) to obtain bonded test pieces.

[0039] Example 4: The adhesive compound prepared in Example 1 was uniformly filled into the predetermined bonding area on the inner surface of the high-temperature vulcanized silicone rubber umbrella skirt sheath using an injection molding process. The umbrella skirt sheath coated with adhesive was then assembled and aligned with the high-strength glazed ceramic and placed in a large injection molding mold. Subsequently, the integrated molding and curing process of step S2 was strictly followed: Pre-curing: held at 70°C for 1.5 hours to allow the adhesive to initially plasticize and adhere tightly to the surface of the mandrel; Stress release: the temperature was slowly increased to 90°C at a rate of 0.5°C / min, and the temperature was maintained in sections. This stage is critical to ensure that the internal stress that may be caused by the difference in the coefficient of thermal expansion between the adhesive and the matrix in the large insulator components is effectively relaxed; Main curing and post-curing: the final cross-linking and network stabilization were completed sequentially at 140°C / 5h and 165°C / 1h.

[0040] After curing, the high-voltage hybrid insulator product with the umbrella skirt sheath reliably connected to the core rod through the optimized adhesive layer is obtained.

[0041] Performance tests were conducted on 110kV voltage level hybrid insulator samples produced according to Example 4: Interface electrical performance: Its interface steep wavefront impulse voltage (FIVT) and power frequency dry and wet withstand voltage tests all passed the national standard requirements in one go, with a large margin, indicating that the electrical integrity of the bonding interface is excellent and there are no air gaps or defects.

[0042] Mechanical load performance: Mechanical load failure test shows that its failure strength is higher than the standard value, and the failure mode is the mandrel breakage, rather than the detachment of the skirt from the mandrel. This directly proves that the mechanical strength of the adhesive layer formed by the adhesive of this invention exceeds the strength of the mandrel body material, meeting the most stringent reliability requirements.

[0043] Accelerated aging assessment: After subjecting the sample to 1000 hours of salt spray testing and 5000 hours of multi-factor aging testing (combined UV, damp heat, and temperature cycling), the adhesive interface was disassembled and inspected. No signs of debonding, cracking, or corrosion were found. Ultrasonic scanning imaging of the adhesive area of ​​the aged sample showed uniform interface signals, indistinguishable from a new, unaged interface, confirming its excellent long-term environmental durability.

[0044] Conclusion: This embodiment demonstrates that applying the adhesive product optimized by the method of this invention to the manufacture of high-voltage hybrid insulators, and molding it through a matched gradient curing process, results in insulator products that exhibit excellent electrical performance, mechanical reliability, and long-term resistance to environmental aging. This achieves a complete performance improvement across the entire chain, from molecular design and material preparation to end-product application, fully fulfilling the invention's objective of ensuring the long-term safe and reliable operation of high-voltage transmission lines.

[0045] Comparative Example 1: Unlike Example 1, the same adhesive was used to directly cure the control sample at 140°C for 5 hours. The remaining steps were the same as in Example 1 and will not be repeated here.

[0046] S3. The specimens of Example 1 and Comparative Example 1 were tested. The initial tensile shear strength of Example 1 reached ≥4.5 MPa, which was significantly improved compared with Comparative Example 1 (3.6 MPa). After 1500 hours of thermo-oxidative aging at 150℃, 1000 hours of humid heat aging at 85℃ / 85%RH, and 1000 hours of UVA-340 ultraviolet aging, the strength retention rates of Example 1 were ≥80%, ≥85%, and ≥82%, respectively, and the boiling water failure time exceeded 500 hours. All aspects of durability were far superior to those of Comparative Example 1.

[0047] Based on the quantitative aging model established by S1, ultrasonic testing (10 MHz longitudinal wave probe) can be used to non-destructively assess the interface condition: the typical sound velocity of a healthy interface is 1000-1200 m / s, and the attenuation coefficient is 5-15 dB / cm; when the sound velocity decreases by more than 10% or the attenuation increases by more than 50%, it can provide an early warning of interface performance degradation. This assessment method enables quantitative judgment of the aging state of the adhesive interface and prediction of its remaining life.

[0048] Comparative Example 2: Unlike Example 1, ordinary α,ω-dihydroxypolydimethylsiloxane raw material was used, without introducing phenyl, trifluoropropyl, or specific hydrolyzable silane groups, but the gradient curing process of Example 1 of this invention was used for curing. The remaining steps are the same as in Example 1, and will not be repeated here.

[0049] Tests showed that the initial tensile shear strength of Comparative Example 2 was 3.9 MPa; after 1500 hours of thermo-oxidative aging at 150°C, the strength retention rate was 52%; after 1000 hours of humid heat aging at 85°C / 85%RH, the strength retention rate was 55%; after 1000 hours of UVA-340 ultraviolet aging, the strength retention rate was 60%; and the boiling failure time was approximately 150 hours. While the initial strength was acceptable, after aging under the same conditions, its strength retention rate was significantly lower than that of Example 1, and even lower than that of Comparative Example 1. This indicates that adhesives lacking specific molecular structure design cannot achieve excellent long-term durability even with advanced processes.

[0050] Comparative Example 3: The same adhesive compound as in Example 1 was used, but the curing process was changed: first, pre-curing was performed at 70°C for 1.5 hours; then, the stress release stage of segmented heat preservation was eliminated, and the temperature was directly and uniformly increased from 70°C to 140°C at a rate of 2°C / min; finally, main curing was performed at 140°C for 5 hours, followed by curing at 165°C for 1 hour. The remaining steps were the same as in Example 1 and will not be repeated here.

[0051] Tests showed that the initial tensile shear strength of Comparative Example 3 was 3.7 MPa; the strength retention rate was 60% after 150°C thermo-oxidative aging for 1500 hours; the strength retention rate was 64% after 1000 hours of 85°C / 85%RH humid heat aging; the strength retention rate was 70% after 1000 hours of UVA-340 ultraviolet aging; and the boiling failure time was approximately 190 hours. Its initial strength and aging resistance were significantly lower than those of Example 1, but equivalent to Comparative Example 1 (one-step method). This indicates that simply controlling the heating rate without providing sufficient holding time for stress release has limited effectiveness.

[0052] Comparative Example 4: Unlike Example 1, after pre-curing at 70°C for 1.5 hours, no intermediate heat preservation stage was set. The temperature was directly raised to 140°C and subjected to main curing for 5 hours. Finally, it was cured at 165°C for 1 hour. The remaining steps are the same as in Example 1, and will not be repeated here.

[0053] Testing revealed that the initial tensile shear strength of Comparative Example 4 was 3.2 MPa (due to high internal stress, resulting in the lowest initial strength); after 1500 hours of thermo-oxidative aging at 150°C, the strength retention rate was 45% (the worst aging performance); after 1000 hours of humid heat aging at 85°C / 85%RH, the strength retention rate was 48%; after 1000 hours of UVA-340 ultraviolet aging, the strength retention rate was 55%; and the boiling water failure time was approximately 120 hours. The strength retention rate, especially after thermal cycling or long-term aging, was significantly worse than that of Example 1 and Comparative Example 1. The decrease in strength retention was most pronounced after thermal cycling or long-term aging. This is because the direct jump from the pre-curing temperature to the main curing temperature led to an excessively rapid cross-linking reaction rate, preventing any release of the generated internal stress and resulting in the accumulation of severe microscopic defects in the interface region. The beneficial technical effects of the optimized method for silicone rubber adhesive for hybrid insulators, the adhesive, and the hybrid insulator provided in this application are as follows: (1) Through molecular dynamics simulation, a quantitative correlation between the molecular structure parameters of the adhesive and the macroscopic interface properties (interfacial bonding energy, aging resistance) is established, realizing directional and rational design at the molecular level; the resulting adhesive molecular structure has both high interfacial compatibility and excellent environmental aging resistance, ensuring the superior performance of the product from the source.

[0054] (2) The gradient curing process developed achieves the coordinated regulation of cross-linking network formation and internal stress relaxation through precise temperature and time control in four stages: pre-curing, stress release, main curing and post-curing. The stress release stage effectively eliminates residual stress at the interface, significantly improving the intrinsic strength and long-term service reliability of the bonding interface.

[0055] (3) By combining the quantitative aging model established by molecular simulation with non-destructive testing technology, a method for early diagnosis and life prediction of the bonding interface state has been formed. This provides key technical support for realizing the intelligent operation and maintenance of hybrid insulators from "periodic maintenance" to "predictive maintenance", which helps to reduce the total life cycle cost.

[0056] It should be noted that, in this document, relational terms such as "first" and "second" are used merely to distinguish one entity or operation from another, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Furthermore, the terms "comprising," "including," or any other variations thereof are intended to cover non-exclusive inclusion, such that a process, method, article, or apparatus that comprises a list of elements includes not only those elements but also other elements not expressly listed, or elements inherent to such a process, method, article, or apparatus. Without further limitation, an element defined by the phrase "comprising one..." does not exclude the presence of other identical elements in the process, method, article, or apparatus that includes said element.

[0057] Finally, it should be noted that the above embodiments are merely examples for clearly illustrating the present invention and are not intended to limit the implementation. Those skilled in the art will recognize that other variations or modifications can be made based on the above description. It is neither necessary nor possible to exhaustively list all possible implementations. However, obvious variations or modifications derived therefrom are still within the scope of protection of this invention.

Claims

1. An optimization method for a hybrid insulator silicone rubber adhesive, characterized in that: Includes the following steps: S1. Construct an interfacial molecular model of high-temperature vulcanized silicone rubber and silicone rubber adhesive, calculate the interfacial binding energy through molecular dynamics simulation, and simulate the aging process under high temperature, high humidity and ultraviolet radiation environment. Based on the interfacial binding energy and aging simulation results, screen and determine the optimal molecular structure of silicone rubber adhesive. S2. The adhesive compound is formulated using the optimal molecular structure determined in step S1, and the adhesive compound is cured using a gradient curing process, which includes a pre-curing stage, a stress release stage, a main curing stage, and a post-curing stage in sequence.

2. The method for optimizing the silicone rubber adhesive for hybrid insulators according to claim 1, characterized in that: In step S1, the optimal molecular structure is a modified siloxane oligomer, wherein the main chain of the modified siloxane oligomer is modified with phenyl or trifluoropropyl groups, the side chain is modified with hydrolyzable silane groups, and the end group is modified with vinyl crosslinking sites.

3. The method for optimizing the silicone rubber adhesive for hybrid insulators according to claim 2, characterized in that: In the modified siloxane oligomer, the structural units of phenyl or trifluoropropyl modified units account for 5%-20% of the total structural units, the side chains containing hydrolyzable silane groups account for 1%-5% of the total side chains, and the end groups containing vinyl groups account for 0.5%-2% of the total end groups.

4. The method for optimizing the silicone rubber adhesive for hybrid insulators according to claim 1, characterized in that: In step S1, the simulated environmental parameters are as follows: the high temperature condition is 150℃-200℃, the high humidity condition is a relative humidity of 85%-95%, and the ultraviolet radiation condition is the use of a UVA-340 fluorescent ultraviolet lamp with an irradiance of 0.35 W / m at a wavelength of 340nm. 2 ~1.5 W / m 2 .

5. The method for optimizing the silicone rubber adhesive for hybrid insulators according to claim 1, characterized in that: The preparation process of the adhesive compound in step S2 includes: Based on the functional group composition corresponding to the optimal molecular structure determined in step S1, select the corresponding cyclosiloxane monomers and carry out ring-opening copolymerization reaction under the action of a catalyst to synthesize modified siloxane polymer-based raw rubber. Based on 100 parts by weight of the raw rubber, add 40-50 parts by weight of fumed silica, 3-5 parts by weight of coloring stabilizer, and 1-2 parts by weight of peroxide curing agent, and mix evenly at room temperature to obtain an adhesive compound with uniform texture and color.

6. The method for optimizing the silicone rubber adhesive for hybrid insulators according to claim 5, characterized in that: The coloring stabilizer is iron oxide red, and the peroxide curing agent is 2,5-dimethyl-2,5-di(tert-butylperoxy)hexane.

7. The method for optimizing the silicone rubber adhesive for hybrid insulators according to claim 5, characterized in that: Based on the functional group composition corresponding to the optimal molecular structure determined in step S1, appropriate cyclosiloxane monomers are selected, and ring-opening copolymerization is carried out under the action of a catalyst to synthesize modified siloxane polymer-based raw rubber, including: Based on the functional group composition corresponding to the optimal molecular structure, octamethylcyclotetrasiloxane and cyclosiloxane monomers containing phenyl or trifluoropropyl groups were selected and combined with silane coupling agents containing hydrolyzable groups. Under the action of a catalyst, a ring-opening copolymerization reaction was carried out to synthesize modified siloxane polymer-based raw rubber with target chain segments and functional groups.

8. The method for optimizing the silicone rubber adhesive for hybrid insulators according to claim 1, characterized in that: The gradient curing process described in step S2 includes: Pre-curing stage: Curing at 60℃-80℃ for 1-2 hours; Stress release stage: The temperature is gradually increased from the pre-curing temperature gradient to 80℃-100℃, and then kept at the temperature in sections within this temperature range for a total duration of 1-3 hours. Main curing stage: Heat to 120℃-150℃ and cure for 4-6 hours; Post-curing stage: Heat treatment at 150℃-180℃ for 1-2 hours.

9. The method for optimizing the silicone rubber adhesive for hybrid insulators according to claim 1, characterized in that: Step S1 also includes: establishing a quantitative relationship model between molecular structure parameters and aging performance.

10. The method for optimizing the silicone rubber adhesive for hybrid insulators according to claim 9, characterized in that: The optimization method further includes step S3: Based on the quantitative relationship model and combined with the non-destructive testing results of the bond interface after curing, the aging state of the bond interface is evaluated.

11. The method for optimizing the silicone rubber adhesive for hybrid insulators according to claim 10, characterized in that: The non-destructive testing includes at least one of ultrasonic testing, X-ray imaging, and dielectric spectrum analysis.

12. The method for optimizing the silicone rubber adhesive for hybrid insulators according to claim 10, characterized in that: In step S1, the molecular dynamics simulation is performed using the COMPASS force field.

13. A hybrid insulator silicone rubber adhesive, characterized in that: The silicone rubber adhesive is prepared by the optimized method for the silicone rubber adhesive for hybrid insulators according to any one of claims 1 to 12.

14. A hybrid insulator, comprising a core rod, a shed sheath, and end metal fittings, wherein the shed sheath is connected to the core rod and / or the metal fittings via an adhesive layer, characterized in that: The adhesive layer is formed by curing the hybrid insulator silicone rubber adhesive of claim 13.